Transfer of Tacit Knowledge towards Innovation - Hartmann, Evi; Seidler‐de Alwis, Ragna (Innovation Management in Global Networks - A Challenge and Chance for Top-Management, 2006)
Purpose The purpose of this paper is to examine the use of tacit knowledge within innovative organizations. It addresses what organizations can do to promote knowledge sharing in order to improve successful innovation. Compared to available research material on explicit knowledge, the use of tacit knowledge within companies is relatively unexplored. The use of tacit knowledge is assessed with special emphasis on its significance and implications in the innovation process.   Design/methodology/approach Existing research is structured with the objective of examining how companies make use of tacit knowledge. Key levers for tacit knowledge management are identified and the positive impact of tacit knowledge on innovation success disclosed.   Findings The role of tacit knowledge in innovation management is analysed. Creation, availability and transfer of tacit knowledge within an organization are highlighted. Competitive advantage will be gained when companies value their tacit knowledge because explicit knowledge is knowledge we are already aware of and is public by its nature. Tacit knowledge can be the source of a huge range of opportunities and potentials that constitute discovery and creativity.   Practical implications As this paper focuses on the transfer of tacit knowledge, barriers to successful knowledge transfer are described and success factors are explored which help to secure and improve the transfer of tacit knowledge.   Originality/value It is proven that tacit knowledge has a crucial influence on the success of innovation processes in companies and plays a vital role as a company resource and success factor.
WiSo-Import:2015-04-20:1267
Keywords: Innovation